2012
DOI: 10.1016/j.jaci.2011.12.974
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between combination inhaled corticosteroid and long-acting β-agonist use and severe asthma exacerbations in a diverse population

Abstract: Background Safety concerns surround the use of long-acting beta agonists (LABA) for the treatment of asthma, even in combination with inhaled corticosteroids (ICS) and particularly in high-risk subgroups. Objective To estimate the effect ICS therapy and fixed-dose ICS/LABA combination therapy on severe asthma exacerbations in a racially diverse population. Methods Inhaled corticosteroid and ICS/LABA exposure was estimated from pharmacy data for patients with asthma age 12 to 56 years who were members of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 34 publications
1
21
0
1
Order By: Relevance
“…BROWN et al [30] treated 741 black patients for 1 year with budesonide/formoterol versus budesonide, and found a decreased exacerbation rate with budesonide/formoterol and a similar safety profile between the two treatments. In a real-life setting, WELLS et al [31] reviewed data from a large health maintenance organisation, including 668 African-Americans, and reported better outcomes (fewer severe exacerbations) with ICS/LABA (dominantly fluticasone/salmeterol) compared with ICS alone, with no safety issues identified.…”
Section: Discussionmentioning
confidence: 99%
“…BROWN et al [30] treated 741 black patients for 1 year with budesonide/formoterol versus budesonide, and found a decreased exacerbation rate with budesonide/formoterol and a similar safety profile between the two treatments. In a real-life setting, WELLS et al [31] reviewed data from a large health maintenance organisation, including 668 African-Americans, and reported better outcomes (fewer severe exacerbations) with ICS/LABA (dominantly fluticasone/salmeterol) compared with ICS alone, with no safety issues identified.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines also indicate that combination ICS and LABA therapy be considered for individuals with this level of asthma severity. However, these recommendations are tempered by conflicting findings in the literature, which suggest both a beneficial (34,35) and detrimental effect (36) of supplemental LABA use, particularly among African American individuals. As a sensitivity analysis in a subset of SAPPHIRE participants with longitudinal prescription information, we found that self-reported African American raceethnicity was still a risk factor for nocturnal symptoms even after accounting for LABA and ICS use.…”
Section: Nocturnal Asthma Rates Between Africanmentioning
confidence: 99%
“…Wells and colleagues 25 estimated the effect of ICS therapy and fixed-dose ICS/LABA combination therapy on severe asthma exacerbations in a racially diverse population through database modeling: 1,828 subjects met the inclusion criteria, 37% were African-American, 46% were treated with ICS therapy alone, and 54% were treated with an ICS/LABA combination. The modeling demonstrated that treatment with ICS/LABA fixed-dose combination therapy appeared to perform as well as or better than ICS treatment alone in reducing severe asthma exacerbations, including multiple high-risk subgroups.…”
Section: Pharmacologymentioning
confidence: 99%